2016
DOI: 10.1371/journal.pone.0160577
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variations of Human Circulating Cell-Free Micro-RNA

Abstract: A 24-hour light and dark cycle-dependent rhythmicity pervades physiological processes in virtually all living organisms including humans. These regular oscillations are caused by external cues to endogenous, independent biological time-keeping systems (clocks). The rhythm is reflected by gene expression that varies in a circadian and specific fashion in different organs and tissues and is regulated largely by dynamic epigenetic and post-transcriptional mechanisms. This leads to well-documented oscillations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 54 publications
0
40
0
Order By: Relevance
“…For the qPCR, a Fluidigm BioMark microfluidic chip system (Fluidigm Corp. USA) allowing duplicate assays for 48 miRNAs in 96 samples in one operation was used. For more technical details please refer to [18]. …”
Section: Methodsmentioning
confidence: 99%
“…For the qPCR, a Fluidigm BioMark microfluidic chip system (Fluidigm Corp. USA) allowing duplicate assays for 48 miRNAs in 96 samples in one operation was used. For more technical details please refer to [18]. …”
Section: Methodsmentioning
confidence: 99%
“…Diurnal variation for miRNAs levels should be considered. However, since samples were collected between morning-noon time and single session was not longer than four hours we can assume that our observation was an effect of hemodialysis and not a physiological change through the time, since diurnal variation occurs mainly between day and night and the change is not more than two-fold [35]. Another limitation arises from discrepancies in fold change between the screening and validation studies.…”
Section: Discussionmentioning
confidence: 93%
“…The diurnal variance of plasma miR-122 levels was reported with up to 2-fold difference between daytime peak and nocturnal sleep (Heegaard, et al 2016). Comparison of plasma miR-122 diurnal variations between healthy individuals and patients, may reveal the mechanistic aspect of some liver diseases.…”
Section: Discussionmentioning
confidence: 97%
“…While efforts were made to reduce the intra-individual variances, studies of plasma miR-122 as DILI biomarkers were reported recently in more negative tones in general, due to its release from hepatocytes in absence of overt cellular injuries (Church and Watkins 2017). Additionally, the diurnal variation of plasma miR-122 (Heegaard, et al 2016) is also a concern for its intraday variance, especially those during daytime. In an attempt to understand what contribute to the high variation of circulating miR-122 measurement, we utilized plasma-direct miRFLP assays (Xie, et al 2015, Zhu, et al 2017 and stress-trained rat models to explore the effects of stress and drugs on plasma miR-122 levels.…”
Section: Introductionmentioning
confidence: 99%